Implementasi Pelatihan dan Pemberdayaan Kelompok Sadar Wisata (Pokdarwis) Berbasis Industri Hospitality di Desa Wisata Setanggor, Lombok Tengah - Jumaidin Jumaidin; Ma'ruf; Muhammad Setyo Nugroho (Pusat Kajian Pariwisata dan Publikasi Jurnal Sekolah Tinggi Pariwisata Mataram, 2023)
The development of tourism villages and the alleviation of poverty are important objectives that can be achieved through training and empowerment programs. This study presents the findings of a program that was conducted in the Setanggor tourism village in collaboration with Universitas Islam Negeri (UIN) Mataram in 2020. The focus of this program was on the Hospitality Industry-based service system and it involved training 11 members of the Setanggor tourism village-based tourism awareness group (Pokdarwis) using qualitative methods. The results of the training showed an increased awareness of the community in serving tourists, which is expected to increase the number of tourist visits to the Setanggor tourism village. This, in turn, will have a positive impact on the motivation of the community to further develop the tourism village. However, the sustainability of tourism villages is contingent on continuous improvement and support from both the central and local governments. Therefore, it is essential to ensure that such programs are ongoing and receive the necessary support so that tourism villages can continue to develop and provide benefits to the community and the country as a whole